Comparative Analysis of Church, Community, and National Park Forests in Biomass Carbon Stock and Climate Change Mitigation in Ethiopia: A Review - Geremew Bitew Sewagegn (International Journal of Forestry Research)
Recently, biophysical, environmental, and economic indicators have provided strong evidence that natural resources in Ethiopia are severely deteriorating due to natural and anthropogenic disturbances. As a result, only small remnant woody species were left around churches, national parks, and some protected community forests through legal protections and religious sanctions. The study aimed to identify the highest biomass carbon-storing forest category for climate change mitigation in Ethiopia. The above- and belowground biomass carbon stock data were collected and extracted from published and unpublished scientific reports based on their relevance and linkage to the topic, publication date, quality of the source, methodological rigor, clarity, and accessibility. The biomass carbon stock variation among each category was analyzed using ANOVA version 20. The mean biomass carbon stock of church, community, and national park forests was 151.80, 303.55, and 160 tons/ha, respectively. According to the result, each forest category has been playing an important role in carbon sequestration and climate change mitigation in the country. The study concludes that community forests exhibit the highest biomass carbon stock and contribute their critical role in climate change mitigation, supporting ecosystem services, and maintaining ecological stability.